1996
DOI: 10.1002/hep.510240401
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Persistence of Hepatitis B Virus Core Gene Deletion Mutants in Renal Transplant Patients Are Associated With End–Stage Liver Disease

Abstract: In renal transplant recipients, chronic hepatitis B virus (HBV) infection often leads to cirrhosis and liver failure. In this study, we investigated whether or not in these patients viral variants would emerge despite immunosuppression, and whether they are associated with a specific course of liver disease. In a population of 552 renal transplant recipients hepatitis B 24 surface antigen (HBsAg)-positive patients were available for a 2-year follow-up. By polymerase chain reaction (PCR) and DNA sequencing, HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 36 publications
(6 reference statements)
4
38
1
Order By: Relevance
“…Liver disease in chronic HBV patients has not only been associated with the presence of specific genotypes, as indicated above, but also with mutations within the precore and core regions of the HBV genome [95, 96] that appear to arise during the course of chronic infection. These mutations have been found in HBV monoinfected patients who had progressive liver disease, who were on immunosuppressive drug therapy [96], and who were associated with enhanced virulence and, in some cases, enhanced replication of the virus [97].…”
Section: Introductionmentioning
confidence: 99%
“…Liver disease in chronic HBV patients has not only been associated with the presence of specific genotypes, as indicated above, but also with mutations within the precore and core regions of the HBV genome [95, 96] that appear to arise during the course of chronic infection. These mutations have been found in HBV monoinfected patients who had progressive liver disease, who were on immunosuppressive drug therapy [96], and who were associated with enhanced virulence and, in some cases, enhanced replication of the virus [97].…”
Section: Introductionmentioning
confidence: 99%
“…6 In a previous study, we showed that HBV with deletions in the C gene is significantly associated with development of HBV-related end-stage liver disease (ESLD) and death in renal transplant recipients. 7 Whereas the former studies reported just single cases without a control group, the latter was focused on 1 subgenomic region of HBV. Therefore, on the HBV genome level, it is still unclear which type of mutation or which combination of mutations is associated with severe liver disease in immunosuppressed patients and thus might play a role in pathogenesis.…”
mentioning
confidence: 99%
“…According to epitope mapping data, amino acid (aa) residues crucial for formation of the immunodominant region lie within the Gly73–Gly94 stretch of the core polypeptide (for references see [4]). Clinical studies have demonstrated that the emergence and accumulation of mutated HBV genomes carrying deletions in the central region of the HBV core gene (C gene) are accompanied by the progression of liver disease in long‐term immunosuppressed renal transplant recipients [8,9]. During immunosuppression such mutated HBV genomes seem to have a selective advantage for replication over wild‐type (wt) genomes [8,10] and can represent up to 90% of the total HBV DNA population in patient sera (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated that the emergence and accumulation of mutated HBV genomes carrying deletions in the central region of the HBV core gene (C gene) are accompanied by the progression of liver disease in long‐term immunosuppressed renal transplant recipients [8,9]. During immunosuppression such mutated HBV genomes seem to have a selective advantage for replication over wild‐type (wt) genomes [8,10] and can represent up to 90% of the total HBV DNA population in patient sera (unpublished data). Preferential appearance of such C gene mutants during immunosuppression makes their possible relation to immune escape mechanisms unlikely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation